Mode of Occurrence of Nepheline Syenites in the Gorkha-Ampipal Area, Central Nepal Lesser Himalaya - Dhital, M. R. (Journal of Nepal Geological Society, 1995)
In the Gorkha-Ampipal area, low-grade metamorphic rocks of the Kuncha Formation are delimited in the north by the Masel Thrust. The Kuncha Formation is characterised by doubly-plunging, en-echelon types of noncylindrical folds which are 2 to 20 km long (essentially in NW-SE direction), and have wavelengths of a few km. Mineral and stretching lineations are gently plunging due NNE or SSW. The hanging wall of the Masel Thrust is represented by garnet-biotite schists and gneisses. The schists and gneisses make up a steeply northward dipping homocline. In contrast to the rocks of the footwall, they are generally gently dipping and constitute several mesoscopic folds. Further north, the homocline is discordantly overlain by the intensely deformed unit of phyllites, graphitic schists, marbles, crystalline limestones, and calcareous quartzites. The Main Central Thrust sharply overrides the latter unit and brings with it gently northward dipping kyanite-garnet-biotite schists, quartzites, feldspathic schists, and mylonitic gneisses.There are several nepheline syenite intrusive bodies in the Kuncha Formation in the vicinity of the villages Harmi Bhnnjyang, Ampipal, Chanp Bhanjyang, Bhulbhule Khar, and Luintel Bhanjyang. Two separate bodies are also encountered at the confluence of the Masel Khola and the Daraundi Khola. The nepheline syenite bodies observed in the study area vary widely in their shape, size, and orientation. The largest pluton is observed in the vicinity of the villages Ampipal and Chanp Bhanjyang. It is about 7.5 km long in NNE-SSW direction and about 2 km wide. The second largest body is observed between the villages Bandre and Luintel Bhanjyang. It is about 2.5 km long approximately in east-west direction and 300 m wide. Numerous other smaller bodies ranging in size from hundreds of m to a few cm also occur in the region. The nephelinesyenites show sharp and irregular contacts with the country rock, they are crosscut by numerous dykes, and occasionally the effect of contact metamorphism is also observed in the country rock.The northeastern part of the largest nepheline syenite pluton (which occurs between Ampipal and Chanp Bhanjyang) is covered by about 500 m thick band of impure marbles. Rare, thin alternations of impure marble with phyllite as well as large (more than 10 m in diameter) scattered marble boulders areseen on the slopes NE of Chanp Bhanjyang, N of Bhulbhule Khar, at the saddle of Lagamkot, and at Khanigaun. The secondary mineralisation in the marbles is represented by magnetite, actinolite, biotite, and chlorite. There exist a few old iron mine workings in the magnetite mineralisation zones. Similar minerals are also seen in the nepheline syenite suggesting a direct relationship between the mineralisation in the nepheline syenite and the marbles. Generally, the nepheline syenite bodies exhibit the same trends of foliation and lineation as those of the country rock, and therefore, they must be intruded before the development of the secondary structures.There are a few hot springs at Bhulbhule Khar, which contain a high amount of H2S gas and sulphur, and are coming through the nepheline syenite. The development of copper as well as other secondary ore minerals and several generations of veins in the country rock, and the presence of hot springs probably indicate a continued hydrothermal activity in that area up to the recent times.